Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus - Korovchinsky, Nikolai M. (Zootaxa, 2018)
Two species of the genus Bythotrephes Leydig, B. brevimanus Lilljeborg and B. cederstrӧmii Schӧdler, are analysed. The former of them is redescribed on the basis of type material and other materials from Northern Europe while the latter one is reevaluated, in comparison with the previous recent investigation which was based on limited material being not enough for the adequate species assessment. The species under consideration were investigated with the application of detailed morphological analysis, including intra- and interpopulation variability and the original scheme of morphometric measurements. The lectotype and paralectotypes of B. brevimanus were selected. Both species are characterized by considerable morphological variability which was especially prominent in taxonomically important features, such as structure and armament of thoracic limbs of first pair (tl I), caudal process, and claws of postabdomen and caudal process. It was concluded that the taxonomic identification of such variable units like B. brevimanus, B. cederstrӧmii and hybrid forms close to the latter species should be based only on comparison of sets of specimens of particular populations; the usage of single specimens can lead to incorrect results. Pedogenesis, in B. brevimanus and in family Cercopagididae in general, was recorded and described for the first time.A new species, B. lilljeborgi, is described based on material from Southern Sweden and Norway. It differs from the closely related species B. longimanus and B. brevimanus in number and size of claws of postabdomen and caudal process.The ranges of the above considered species overlap, especially prominently in North-Western Europe where all three species under consideration co-occur. B. brevimanus dominates in the Circumbaltic region and eastward through Central European Russia and the Ural Mountain region, possibly to the Yenisei River which requires further confirmation. B. cederstrӧmii is distributed further to the east, being recorded in Central Yakutia (Eastern Siberia). Data on co-occurrence of Bythotrephes species are limited and not always adequate because identification of taxa was often confused. Based on the information contained in the present paper, in particular the reevaluation of B. cederstrӧmii taxonomy, it may be suggested that both interspecific hybrid forms and B. cederstrӧmii s. str. could have invaded North American inland waters.